Electrochemical fluorescence switching from a patternable poly(1,3,4-oxadiazole) thin film - Seo, Seogjae; Kim, Yuna; You, Jungmok; Sarwade, Bhimrao D.; Wadgaonkar, Prakash P.; Menon, Shamal K.; More, Arvind S.; Kim, Eunkyoung (Macromolecular Rapid Communications, 2011)
A highly soluble poly(1,3,4-oxadiazole) (POD) substituted with long alkyl chains was examined for electrochemical fluorescence switching. The high solubility of the polymers enabled a simple fabrication of an electrochemical cell, which showed reversible fluorescence switching between dark (n-doping) and bright (neutral) states with a maximum on/off ratio of 2.5 and a cyclability longer than 1000 cycles. Photochemical cleavage of the oxadiazole in POD allowed photo-patterning of the POD film upon exposure to UV source. The patterned POD films displayed patterned image reversibly under a step potential of +1.8/-1.8V.
Keywords: fluorescence; lithography; Luminescence; photochemistry; switching device